Multiwall Carbon Nanotube (MWCNT), MWCNT / Carbon Black (CB) And MWCNT / Silica Hybird Fillers Filled Natural Rubber Nanocomposites - Ramly, Ahmad Faizal Mohd (2011)
Carbon nanotubes are an intriguing reinforcement for polymers because of their unique mechanical proprties and extremely large surface area per unit volume. this MWCNTs are added in oder to get a sustantial improvement in the physical and mechanical propeties of rubber compound. In these present studies, MWCNTs are added as a filler in natural rubber (NR) matrix.